Phenotypic and genetic parameters for growth traits of Abergelle goat in community-based breeding program scale up village - Abebe, Yeshiwas Walle; Meberatie, Wossenie Shibabaw; Wondie, Zeleke Tesema (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Abstract—-the objective of this research was to estimate genetic and phenotypic parameters for growth and milk production traits of Abergelle goats in community-based breeding program (CBBP) scale up village. The data used in the study was six years (2018-2023) data from the established village of goat community based breeding program area. The traits studied were, birth weight (BWT), weight at three months (TMWT), weight at six months (SMWT), weight at nine months (NMWT), yearling weight (YWT), direct heritability for growth and milk traits was computed by using WOMBAT software. Univariate mixed animal model was applied to estimate genetic parameters. Bivariate analysis was utilized to estimate correlations between traits. The overall least square mean of body weights ± standard errors (LSM±SE) for BWT, TMWT, SMWT, NMWT, and YWT were 2.3±0.04, 7.5±0.03, 8.8±0.040, 12.1±0.067, and 15.3±0.092 kg, respectively. The direct heritability estimates for BWT, TMWT, SMWT, NMWT, and YWT were 0.34±0.070, 0.45±0.062, 0.40±0.040, 0.42±0.07and 0.41±0.14, respectively. Phenotypic correlation of BWT with TMWT, SMWT, NMWT and YWT was low but that of TMWT-SMWT, SMWT-NMWT and NMWT-YWT was high and positive. The genetic correlations of birth weight with the studied growth traits were moderate but higher correlations were found among the other growth traits (SMWT, NMWT, and YWT), indicating as one of these traits increases; the others tend to increase as well. Therefore, birth weight as growth trait had no strong relation with later stages of growth traits in this study for Abergelle goat in scale up community based breeding programs.